CRX-527 induced differentiation of HSCs protecting the intestinal epithelium from radiation damage - Liu, Dongshu; Dong, Suhe; Liu, Cong; Du, Jicong; Wang, Sinian; Yu, Huijie; Li, Wei; Chen, Zhongmin; Peng, Renjun; Jiang, Qisheng; Zou, Mengying; Li, Fengsheng; et al. (Frontiers in Immunology, 2022)
Recently, Toll-like receptors (TLRs) have been extensively studied in radiation damage, but the inherent defects of high toxicity and low efficacy of most TLR ligands limit their further clinical transformation. CRX-527, as a TLR4 ligand, has rarely been reported to protect against radiation. We demonstrated that CRX-527 was safer than LPS at the same dose in vivo and had almost no toxic effect in vitro. Administration of CRX-527 improved the survival rate of total body irradiation (TBI) to 100% in wild-type mice but not in TLR4-/- mice. After TBI, hematopoietic system damage was significantly alleviated, and the recovery period was accelerated in CRX-527-treated mice. Moreover, the stimulation of CRX-527 significantly increased the proportion and number of LSK cells and promoted their differentiation into macrophages, activating immune defense. Furthermore, we proposed an immune defense role for hematopoietic differentiation in the protection against intestinal radiation damage, and confirmed that macrophages invaded the intestines through peripheral blood to protect them from radiation damage. Meanwhile, CRX-527 maintained intestinal function and homeostasis, promoted the regeneration of intestinal stem cells, and protected intestinal injury from lethal dose irradiation. Furthermore, TLR4-/- mice were used to confirm that CRX-527 protects the hematopoietic and intestinal systems from irradiation through the activation of TLR4-related pathways.